Effect of the physiological state of Criollo goats on the botanical composition of their diet in NE Mendoza, Argentina - Allegretti, Liliana Inés (2012)
The botanical composition of the diet and species preference of grazing goats in different physiological states were evaluated in the autumn and winter seasons. The study was performed in a desert rangeland in the northeast (NE) Mendoza region in Argentina. Food availability was estimated from forage species cover. Rectal grab faecal samples were collected from goats, and the botanical composition of the goat diet was determined using a microhistological technique. Goat preferences for each species consumed were calculated based on Ivlev?s index. Nutritional composition and secondary compounds of forage species were determined. Correlations between diet and availability; and between goat preference and nutritional composition of forage species were also estimated. The habitat consisted of a dominant woody stratum associated with an herb stratum primarily composed of grasses. Goats in different physiological states utilised a significantly higher proportion of woody vegetation compared to grass (p < 0.01). When grass availability was high (autumn), the herb stratum was more utilised by pregnant and lactating goats than by dry goats (p < 0.05). In the winter, the diet of lactating goats consisted of more Atriplex lampa compared to the diet of dry goats (p<0.05), probably due to the high crude protein content of the plant. Goats consumed forage species with highly variable total phenol and tannin contents, which did not negatively affect selection. Correlations between diet and availability were high in the winter for dry (rs = 0.88, p < 0.02), pregnant (rs = 0.93, p < 0.01) and lactating goats (rs = 0.97, p < 0.01) but were not significant in the autumn. A significant correlation between preference and crude protein was shown during the autumn season for pregnant and lactating goats (rs = 0.6, p < 0.05). Forage availability was the main factor influencing diet selection in this arid environment. When food availability was not a limiting factor, goats selected a diet that most closely matched their nutritional requirements. Physiological state modified nutrient requirements and affected diet selection in that pregnant and lactating goats selected forage species with high protein contents.